Associations of long-term exposure to environmental noise and outdoor light at night with age at natural menopause in a US women cohort. Issue 3 (5th June 2021) - Li, Huichu; Hart, Jaime E.; Mahalingaiah, Shruthi; Nethery, Rachel C.; James, Peter; Bertone-Johnson, Elizabeth; Schernhammer, Eva; Laden, Francine
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Previous studies have suggested noise, especially at night time, and light at night (LAN) could cause neuroendocrine disturbance and circadian disruption, which may lead to ovarian follicle atresia and earlier onset of menopause. However, no study to date has directly investigated the associations of exposure to these factors and menopausal age. Methods: Premenopausal women from the Nurses' Health Study II (NHS II) were followed from age 40 through 2015. Median daytime and nighttime anthropogenic noise and outdoor LAN exposure were measured from a geospatial prediction model and satellite images, respectively, at residential addresses throughout the follow-up. Time-varying Cox proportional hazard models were used to calculate the hazard ratios and 95% confidence intervals, adjusting for individual lifestyle, reproductive history, and neighborhood socioeconomic factors. Possible effect modification by region, smoking status, body mass index, race/ethnicity, history of rotating shift work, and census tract population density and median income was examined. Results: A total of 63, 380 of 105, 326 women self-reported natural menopause during 1, 043, 298 person-years of follow-up. No associations were found for noise (both daytime and nighttime) and outdoor LAN exposure with age at natural menopause (hazard ratios = 0.99–1.00) in the fully adjusted models. Sensitivity analyses showed similar null associations. No meaningful effect modification was found for region, smoking status, body mass index, race/ethnicity, history of rotating shift work, and census tract socioeconomic measures in stratified analyses. Conclusion: No associations were found between environmental noise and outdoor LAN exposure in mid-adulthood and menopausal age in this cohort of US women.